CO2-assisted phosphorus extraction from poultry litter and selective recovery of struvite and potassium struvite. (15th October 2018) - Shashvatt, Utsav; Benoit, Josh; Aris, Hannah; Blaney, Lee
Abstract: Phosphorus recovery from industrialized poultry operations is necessary to ensure sustainable waste management and resource consumption. To realize these goals, an innovative, two-stage process chemistry has been developed to extract nutrients from poultry litter and recover value-added products. Over 75% phosphorus extraction was achieved by bubbling carbon dioxide into poultry litter slurries and adding strong acid to reach pH 4.5–5.5. After separating the nutrient-deficient poultry litter solids and the nutrient-rich liquid, the extract pH was increased through aeration and strong base addition. Over 95% of the extracted phosphorus was recovered as solid precipitate at pH 8.5–9.0. High-purity struvite and potassium struvite products were selectively recovered through pH control, introduction of a calcium-complexing agent, and addition of magnesium chloride. The nitrogen-to-phosphorus-to-potassium (NPK) ratio of the recovered solids was controlled through aeration and pH adjustment. Precipitation at pH 8.5–9.0 and 10.5–11.0 resulted in NPK ratios of 2.0:1.0:0.1 and 0.9:1.0:0.2, respectively. The process effluent was effectively recycled as makeup water for the subsequent batch of poultry litter, thereby decreasing water consumption and increasing overall nutrient recovery. Sequencing batch operation yielded greater than 70% phosphorus recovery within a 45-min process, demonstrating the potential for this technology to alleviate nutrient pollution in agricultural settings and generate an alternative supply of phosphorus fertilizers. Graphical abstract: Image 1 Highlights: CO2 and HCl addition provided >75% phosphorus extraction from poultry litter. Aeration and NaOH addition yielded >95% precipitation of phosphorus-laden solids. Struvite and potassium struvite were selectively recovered from poultry litter. Liquid process effluent was effectively reused, decreasing overall water usage. Over 70% phosphorus recovery was achieved in a 45 min sequencing batch operation.